Political Economy Implications of Electric Vehicle Policies: A Bibliometric Analysis - Achluddin Ibnu Rochim; Ghulam Maulana Ilman; Hasan Ismail (Society, 2025)
This article examines the current landscape of research on electric vehicle (EV) policy, emphasizing the critical yet underexplored role of political economy. While existing studies predominantly focus on infrastructure development, sustainability, and subsidy policies, there is a notable lack of attention to the political dynamics and economic influences that shape EV initiatives. This study investigates the implications of EV policies through a bibliometric analysis, utilizing tools such as VOSviewer to map and analyze academic literature on the topic. It provides a comprehensive overview of key themes, including highly cited research, author contributions, country-level outputs, institutional engagement, and network analyses such as co-citation, bibliographic coupling, and keyword co-occurrence. The study also highlights the countries that have significantly contributed to the field. Findings reveal that integrating political economy perspectives is essential for developing comprehensive and equitable EV policies that address the diverse needs of stakeholders. Ultimately, this article calls for a more holistic approach to EV research, advocating a deeper exploration of the interplay between political and economic forces to enhance the effectiveness and inclusivity of electric mobility initiatives. This study contributes to the growing body of knowledge on EV policy frameworks by offering insights into the complex dynamics of political economy, thereby informing policymakers and researchers seeking to navigate the challenges of sustainable mobility transitions.